2017
DOI: 10.1186/s12887-017-0939-0
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices of pediatricians on infantile colic in the Middle East and North Africa region

Abstract: BackgroundRegional evidence-based guidelines for the prophylaxis and management of infantile colic are not available for the Middle East and North Africa (MENA) region. The Allied Against Infantile Functional GI Disorders (ACT) Working Group was created in January, 2015 to determine the knowledge gaps and the current management practices of infantile colic by physicians in the MENA region. The ACT group determined the need for a survey to address these questions. The objectives of the survey were to highlight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
2
12
0
2
Order By: Relevance
“…This statement is supported by a study developed in the Middle East and north Africa, which demonstrated that physicians prioritize as a strategy to promote the tranquility of parents. Other actions are related to breastfeeding and the use of formulas, as well as natural therapies (21) .…”
Section: Discussionmentioning
confidence: 99%
“…This statement is supported by a study developed in the Middle East and north Africa, which demonstrated that physicians prioritize as a strategy to promote the tranquility of parents. Other actions are related to breastfeeding and the use of formulas, as well as natural therapies (21) .…”
Section: Discussionmentioning
confidence: 99%
“…In one study, pediatricians and general practitioners across middle-eastern and northern Africa have found that 25% of parents reported giving their babies herbal medications, and 0.8% reported cauterizing their babies before seeking medical help to relieve infantile colic. 18 Another study has reported that 51.8% of mothers use herbal medications for infantile colic. 19 Anzaroot ( Astragalus sarcocolla Dymock) is a well-known herb in KSA used to treat infantile colic, abdominal pain, and the common cold.…”
Section: Challenges In Traditional Medicine Advocacymentioning
confidence: 99%
“…Although clear estimates from the Middle East and North Africa (MENA) region are lacking, available data point toward a much higher prevalence of FGIDs. In a recent survey of pediatricians from the MENA region, the majority of the participants stated that the prevalence of infant colic <4 months of age exceeded 40% [ 9 ]. A survey of Saudi mothers found that their major reasons for changing an infant formula were colic and gas (32%), constipation (23.6%), and gastroesophageal reflux (20.4%) [ 10 ].…”
Section: Fgid Burdenmentioning
confidence: 99%